NILAI PENDIDIKAN KARAKTER DALAM NOVEL AYAH KARYA ANDREA HIRATA: NILAI RELIGIUS DAN NILAI KERJA KERAS - Ellawati Ellawati; Susi Darihastining; Henny Sulistyowati (FKIP, Universitas Palangka Raya, 2023)
This study aims to determine the values ​​of character education in the novel Ayah by Andrea Hirata. This research is focused on analyzing the values ​​of religious character education and hard work in the novel Ayah. This research was conducted using a qualitative descriptive method. The value of character education is an effort made so that a person can grow and live together with other people. The data source for this research is the novel Ayah by Andrea Hirata. The data collection technique for this research is document or text study. The data analysis technique for this research is analysis. Checking the validity of findings is a technique of persistence. The results of data analysis show that religious values ​​in the novel Ayah by Andrea Hirata are expressed by the author in words that show attitudes and behaviors that draw closer to God, are grateful for all that God has given and understand all forms of gifts and are obedient in carrying out the religion they adhere to. Meanwhile, the results of data analysis in the form of the value of hard work are expressed by the author by showing the character trying earnestly in working hard.